INFORMATION TECHNOLOGY PERSPECTIVE OF QS. AL-JATSIAH VERSE 13 - Azmy Ali Muchtar (LP3M Universitas Sains Al Qur'an, 2023)
Globalization is one result of technological progress. The amount of incoming information has a negative impact on society. This is where the role of religion becomes very important in regulating and controlling the attitudes and behavior of its people so as not to fall into negative things. Technological progress that is not based on and is not accompanied by religion will be in vain, in fact it can backfire that can strike back. Basically, Islam with all its teachings and noble values is a very important component which balances technological progress. So these noble teachings and values must be instilled in the nation's children from an early age. One way is to always implement Islamic education in schools and society. The purpose of writing this article is to find out how QS.Al-Jatsiyah's perspective on information technology, how information technology should be used in the world of Islamic Education and to find out what are the other arguments in the Al-Qur'an and Hadith related to information technology . The result of this article is the Word of God in surah Al-Jatsiyah Verse 13 the sentence